When are investment subsidies crucial for investments? - Mika Haapanen; Anu Tokila; Jari Ritsilä (European Regional Science Association (ERSA), 2005)
EU enlargement to the less developed countries in Central and Eastern Europe is forcing policy makers to reconsider the role of business subsidies in the EU. For example, to what extent the use of investment subsidies should be allowed in the future? Which regions should be supported? In this paper we study conditions under which investment subsidy is a necessary requirement for project implementation in Finland. Empirical analysis is conducted using micro level data on investment projects of private sector firms. The data set comprises 1,836 projects that received public investment subsidies between 2001 and 2003. Our results show that the necessity of the investment subsidies is strongly dependent on the location of the firm as well as on the size of the firm and the investment project.
Keywords: 330